Cholangiocarcinoma in patients with primary sclerosing cholangitis. Issue 2 (March 2020) - Fung, Brian M.; Tabibian, James H.
Abstract : Purpose of review: Primary sclerosing cholangitis (PSC) is a rare cholestatic liver disease characterized by progressive fibroinflammatory destruction of the intrahepatic and/or extrahepatic bile ducts. It is associated with a significantly increased risk of malignancy, particularly cholangiocarcinoma (CCA). In this review, we discuss what is currently known about the epidemiology of and risk factors for CCA in PSC as well as recent advances in its prevention, diagnosis, and surveillance. Recent findings: An area of major focus has been finding novel biomarkers (in serum, bile, and urine) for CCA. With the advancement of computing power, metabolomic and proteomic approaches, among other methods, may provide enhanced capability for differentiating between benign and malignant bile duct disease. Another area of focus has been the approach to CCA surveillance in PSC; a recent study has found that CCA surveillance in patients with PSC is associated with improved outcomes, including increased survival, thus advocating for its importance. Summary: Despite ongoing advancements in the study of PSC-associated CCA, early diagnosis of CCA remains difficult, treatment options are limited, and prognosis is often consequently poor. Continued research in the development of high-accuracy diagnostic tools, novel biomarkers, and surveillance techniques may help to increase the likelihood of diagnosing CCA at earlier stages, when therapeutic options have the highest likelihood of resulting in cure.